Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's solve each equation one by one and verify the results:
1. [tex]\(3x = 2x + 18\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ 3x - 2x = 18 \][/tex]
Step 2: Simplify.
[tex]\[ x = 18 \][/tex]
So, the solution is [tex]\( x = 18 \)[/tex].
2. [tex]\(5t - 3 = 3t - 5\)[/tex]
Step 1: Move all [tex]\(t\)[/tex] terms to one side and constants to the other side.
[tex]\[ 5t - 3t = -5 + 3 \][/tex]
Step 2: Simplify.
[tex]\[ 2t = -2 \][/tex]
[tex]\[ t = -1 \][/tex]
So, the solution is [tex]\( t = -1 \)[/tex].
3. [tex]\(5x + 9 = 5 + 3x\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 5x - 3x = 5 - 9 \][/tex]
Step 2: Simplify.
[tex]\[ 2x = -4 \][/tex]
[tex]\[ x = -2 \][/tex]
So, the solution is [tex]\( x = -2 \)[/tex].
4. [tex]\(4z + 3 = 6 + 2z\)[/tex]
Step 1: Move all [tex]\(z\)[/tex] terms to one side and constants to the other side.
[tex]\[ 4z - 2z = 6 - 3 \][/tex]
Step 2: Simplify.
[tex]\[ 2z = 3 \][/tex]
[tex]\[ z = \frac{3}{2} \][/tex]
So, the solution is [tex]\( z = \frac{3}{2} \)[/tex].
5. [tex]\(2x - 1 = 14 - x\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 2x + x = 14 + 1 \][/tex]
Step 2: Simplify.
[tex]\[ 3x = 15 \][/tex]
[tex]\[ x = 5 \][/tex]
So, the solution is [tex]\( x = 5 \)[/tex].
6. [tex]\(8x + 4 = 3(x - 1) + 7\)[/tex]
Step 1: Expand and simplify.
[tex]\[ 8x + 4 = 3x - 3 + 7 \][/tex]
[tex]\[ 8x + 4 = 3x + 4 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ 8x - 3x = 4 - 4 \][/tex]
[tex]\[ 5x = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
So, the solution is [tex]\( x = 0 \)[/tex].
7. [tex]\(x = \frac{4}{5}(x + 10)\)[/tex]
Step 1: Distribute the factor on the right-hand side.
[tex]\[ x = \frac{4}{5}x + 8 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ x - \frac{4}{5}x = 8 \][/tex]
[tex]\[ \frac{1}{5}x = 8 \][/tex]
Step 3: Simplify.
[tex]\[ x = 8 \cdot 5 \][/tex]
[tex]\[ x = 40 \][/tex]
So, the solution is [tex]\( x = 40 \)[/tex].
8. [tex]\(\frac{2x}{3} + 1 = \frac{7x}{15} + 3\)[/tex]
Step 1: Clear the fractions by finding a common denominator (15).
[tex]\[ 10x + 15 = 7x + 45 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 10x - 7x = 45 - 15 \][/tex]
[tex]\[ 3x = 30 \][/tex]
[tex]\[ x = 10 \][/tex]
So, the solution is [tex]\( x = 10 \)[/tex].
9. [tex]\(2y + \frac{5}{3} = \frac{26}{3} - y\)[/tex]
Step 1: Multiply through by 3 to clear the fractions.
[tex]\[ 6y + 5 = 26 - 3y \][/tex]
Step 2: Move all [tex]\(y\)[/tex] terms to one side and constants to the other side.
[tex]\[ 6y + 3y = 26 - 5 \][/tex]
[tex]\[ 9y = 21 \][/tex]
[tex]\[ y = \frac{21}{9} \][/tex]
[tex]\[ y = \frac{7}{3} \][/tex]
[tex]\[ y = 2.333 \][/tex]
So, the solution is [tex]\( y = 2.333 \)[/tex].
10. [tex]\(3m = 5m - \frac{8}{5}\)[/tex]
Step 1: Move all [tex]\(m\)[/tex] terms to one side.
[tex]\[ 3m - 5m = - \frac{8}{5} \][/tex]
[tex]\[ -2m = - \frac{8}{5} \][/tex]
Step 2: Simplify and solve for [tex]\(m\)[/tex].
[tex]\[ m = \frac{8}{10} \][/tex]
[tex]\[ m = 0.8 \][/tex]
So, the solution is [tex]\( m = 0.8 \)[/tex].
Thus, the solutions are:
1. [tex]\( x = 18 \)[/tex]
2. [tex]\( t = -1 \)[/tex]
3. [tex]\( x = -2 \)[/tex]
4. [tex]\( z = \frac{3}{2} \)[/tex]
5. [tex]\( x = 5 \)[/tex]
6. [tex]\( x = 0 \)[/tex]
7. [tex]\( x = 40 \)[/tex]
8. [tex]\( x = 10 \)[/tex]
9. [tex]\( y = 2.333 \)[/tex]
10. [tex]\( m = 0.8 \)[/tex]
1. [tex]\(3x = 2x + 18\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ 3x - 2x = 18 \][/tex]
Step 2: Simplify.
[tex]\[ x = 18 \][/tex]
So, the solution is [tex]\( x = 18 \)[/tex].
2. [tex]\(5t - 3 = 3t - 5\)[/tex]
Step 1: Move all [tex]\(t\)[/tex] terms to one side and constants to the other side.
[tex]\[ 5t - 3t = -5 + 3 \][/tex]
Step 2: Simplify.
[tex]\[ 2t = -2 \][/tex]
[tex]\[ t = -1 \][/tex]
So, the solution is [tex]\( t = -1 \)[/tex].
3. [tex]\(5x + 9 = 5 + 3x\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 5x - 3x = 5 - 9 \][/tex]
Step 2: Simplify.
[tex]\[ 2x = -4 \][/tex]
[tex]\[ x = -2 \][/tex]
So, the solution is [tex]\( x = -2 \)[/tex].
4. [tex]\(4z + 3 = 6 + 2z\)[/tex]
Step 1: Move all [tex]\(z\)[/tex] terms to one side and constants to the other side.
[tex]\[ 4z - 2z = 6 - 3 \][/tex]
Step 2: Simplify.
[tex]\[ 2z = 3 \][/tex]
[tex]\[ z = \frac{3}{2} \][/tex]
So, the solution is [tex]\( z = \frac{3}{2} \)[/tex].
5. [tex]\(2x - 1 = 14 - x\)[/tex]
Step 1: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 2x + x = 14 + 1 \][/tex]
Step 2: Simplify.
[tex]\[ 3x = 15 \][/tex]
[tex]\[ x = 5 \][/tex]
So, the solution is [tex]\( x = 5 \)[/tex].
6. [tex]\(8x + 4 = 3(x - 1) + 7\)[/tex]
Step 1: Expand and simplify.
[tex]\[ 8x + 4 = 3x - 3 + 7 \][/tex]
[tex]\[ 8x + 4 = 3x + 4 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ 8x - 3x = 4 - 4 \][/tex]
[tex]\[ 5x = 0 \][/tex]
[tex]\[ x = 0 \][/tex]
So, the solution is [tex]\( x = 0 \)[/tex].
7. [tex]\(x = \frac{4}{5}(x + 10)\)[/tex]
Step 1: Distribute the factor on the right-hand side.
[tex]\[ x = \frac{4}{5}x + 8 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side.
[tex]\[ x - \frac{4}{5}x = 8 \][/tex]
[tex]\[ \frac{1}{5}x = 8 \][/tex]
Step 3: Simplify.
[tex]\[ x = 8 \cdot 5 \][/tex]
[tex]\[ x = 40 \][/tex]
So, the solution is [tex]\( x = 40 \)[/tex].
8. [tex]\(\frac{2x}{3} + 1 = \frac{7x}{15} + 3\)[/tex]
Step 1: Clear the fractions by finding a common denominator (15).
[tex]\[ 10x + 15 = 7x + 45 \][/tex]
Step 2: Move all [tex]\(x\)[/tex] terms to one side and constants to the other side.
[tex]\[ 10x - 7x = 45 - 15 \][/tex]
[tex]\[ 3x = 30 \][/tex]
[tex]\[ x = 10 \][/tex]
So, the solution is [tex]\( x = 10 \)[/tex].
9. [tex]\(2y + \frac{5}{3} = \frac{26}{3} - y\)[/tex]
Step 1: Multiply through by 3 to clear the fractions.
[tex]\[ 6y + 5 = 26 - 3y \][/tex]
Step 2: Move all [tex]\(y\)[/tex] terms to one side and constants to the other side.
[tex]\[ 6y + 3y = 26 - 5 \][/tex]
[tex]\[ 9y = 21 \][/tex]
[tex]\[ y = \frac{21}{9} \][/tex]
[tex]\[ y = \frac{7}{3} \][/tex]
[tex]\[ y = 2.333 \][/tex]
So, the solution is [tex]\( y = 2.333 \)[/tex].
10. [tex]\(3m = 5m - \frac{8}{5}\)[/tex]
Step 1: Move all [tex]\(m\)[/tex] terms to one side.
[tex]\[ 3m - 5m = - \frac{8}{5} \][/tex]
[tex]\[ -2m = - \frac{8}{5} \][/tex]
Step 2: Simplify and solve for [tex]\(m\)[/tex].
[tex]\[ m = \frac{8}{10} \][/tex]
[tex]\[ m = 0.8 \][/tex]
So, the solution is [tex]\( m = 0.8 \)[/tex].
Thus, the solutions are:
1. [tex]\( x = 18 \)[/tex]
2. [tex]\( t = -1 \)[/tex]
3. [tex]\( x = -2 \)[/tex]
4. [tex]\( z = \frac{3}{2} \)[/tex]
5. [tex]\( x = 5 \)[/tex]
6. [tex]\( x = 0 \)[/tex]
7. [tex]\( x = 40 \)[/tex]
8. [tex]\( x = 10 \)[/tex]
9. [tex]\( y = 2.333 \)[/tex]
10. [tex]\( m = 0.8 \)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.